Aporophobic and Homeless Victimisation—the Case of Ghent - García Domínguez, Isabel (European journal on criminal policy and research, 2024)
Aporophobia, the rejection of poor people, is a major social problem with known harmful consequences, especially for the most excluded in our society, i.e., homeless people. However, this phenomenon has been only rarely studied using testable means on the ground. This article reports on empirical research conducted on a sample of homeless people in Ghent, Belgium. The principal objective was to analyse aporophobic discriminatory incidents and hate crimes which were experienced by around 50% of the respondents. The most common offences were property crimes, particularly thefts and robberies, with the belief being that the perpetrators were motivated to perform these crimes as they saw this particular demographic group as more helpless and vulnerable. Moreover, the victims usually experienced more than one crime and different typologies. Unfortunately, underreporting was pronounced. It is therefore necessary to increase the visibility of these crimes and the reporting rate, as well as to reduce victimisation. To this end, it is essential to know the real scope of such crimes and their characteristics.